What is the Value of the Okun Coefficient - Tavéra , Christophe; Perman , Roger; Stephan , Gaëtan (Studia Oeconomica Posnaniensia, 2026)
We selected a sample of 522 estimates of the Okun’s Law coefficient from literature to uncover the reasons for the differences in empirical results across studies and to estimate the ’true’ OLC with meta-regression methodology. We show that there is evidence of both type I and type II bias amongst the papers studied. Taking into account those biases and then evaluating the 95% confidence intervals of the true effects estimated with various methodologies, we find that the estimated true OLC vary between a minimum value of -0,40 and a maximum value of -0,12. Moreover, the estimated OLCs are significantly larger (in absolute value) with models using regional data or a linear time trend filtering procedure. On the other hand we find that lower absolute values of the OLC are obtained with models using quarterly (or semestrial) data bases, data for developing countries, or non-linear models.